Time trends in childhood and adolescent obesity in England from 1995 to 2007 and projections of prevalence to 2015. Issue 2 (7th January 2010) - Stamatakis, E; Zaninotto, P; Falaschetti, E; Mindell, J; Head, J
Abstract : Background: The aim was to examine the 1995–2007 childhood and adolescent obesity trends and project prevalence to 2015 by age group and social class. Methods: Participants were children aged 2–10 and adolescents aged 11–18 years from general population households in England studied using repeated cross-sectional surveys. Obesity was computed using international standards. Prevalence projections to 2015 were based on extrapolation of linear and non-linear trends. Results: Obesity prevalence increased from 1995 to 2007 from 3.1% to 6.9% among boys, and 5.2% to 7.4% among girls. There are signs of a levelling off trend past 2004/5. Assuming a linear trend, the 2015 projected obesity prevalence is 10.1% (95% CI 7.5 to 12.6) in boys and 8.9% (5.8 to 12.1) in girls, and 8.0% (4.5, 11.5) in male and 9.7% (6.0, 13.3) in female adolescents. Projected prevalence in manual social classes is markedly higher than in non-manual classes [boys: 10.7% (6.6 to 14.9) vs 7.9% (3.7 to 12.1); girls: 11.2% (7.0 to 15.3) vs 5.4% (1.3 to 9.4); male adolescents: 10.0% (5.2 to 14.8) vs 6.7% (3.4 to 10.0); female adolescents: 10.4% (5.0 to 15.8) vs 8.3% (4.3 to 12.4)]. Conclusion: If the trends in young obesity continue, the percentage and numbers of obese young people in England will increase considerably by 2015 and the existing obesity gap between manual and non-manual classes will widen further. This highlights the need for public health action to reverse recent trends and narrow social inequalities in health.